2022
DOI: 10.1186/s10020-022-00448-x
|View full text |Cite
|
Sign up to set email alerts
|

Lansoprazole-induced osteoporosis via the IP3R- and SOCE-mediated calcium signaling pathways

Abstract: Background Many clinical studies have shown a correlation between proton pump inhibitors (PPIs) and osteoporosis or fractures. The purpose of this study was to establish a murine model of chronic oral PPI administration to verify whether PPIs caused bone metabolic impairment and investigate the relevant molecular mechanism underlying the effects of PPIs on MC3T3-E1 murine osteoblasts. Methods A lansoprazole-induced bone loss model was used to inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…ER stress-mediated osteoblast apoptosis is driven by an increase in the intracellular Ca 2+ concentration [ 101 ]. An increased intracellular Ca 2+ disrupts Ca 2+ homeostasis, leading to Ca 2+ overload [ 102 ] and excessive ER stress103 and inducing osteoblast apoptosis [ 104 , 105 ]. Furthermore, micronutrients such as cadmium [ 106 ], fluorine [ 107 , 108 ], and iron [ 109 ] initiate the ER stress apoptosis pathway by increasing intracellular Ca 2+ .…”
Section: Effects Of Er Stress Pathways On Osteogenesismentioning
confidence: 99%
“…ER stress-mediated osteoblast apoptosis is driven by an increase in the intracellular Ca 2+ concentration [ 101 ]. An increased intracellular Ca 2+ disrupts Ca 2+ homeostasis, leading to Ca 2+ overload [ 102 ] and excessive ER stress103 and inducing osteoblast apoptosis [ 104 , 105 ]. Furthermore, micronutrients such as cadmium [ 106 ], fluorine [ 107 , 108 ], and iron [ 109 ] initiate the ER stress apoptosis pathway by increasing intracellular Ca 2+ .…”
Section: Effects Of Er Stress Pathways On Osteogenesismentioning
confidence: 99%
“…Therefore, PPI-related bone fragility might be determined by the impairment of the repair mechanisms for bone microfractures [6,7]. In particular, Cheng et al identified that lansoprazole, a commonly used PPI, could inhibit the P-type ATPases SERCA and Ca 2+ -ATPase, leading to an increase in Ca 2+ in osteoblasts and inducing endoplasmic reticulum stress and apoptosis; furthermore, blocking the increase in intracellular calcium had a significant protective effect against osteoblast apoptosis [8]. Data on the effect of PPIs on osteoporotic fracture risk have, however, been divergent.…”
Section: Introductionmentioning
confidence: 99%
“…(12) A recent in vitro study using the mouse osteoblast cell line MC3T3-E1 showed that lansoprazole could lead to intracellular calcium overload, inducing endoplasmic reticulum stress and causing osteoblast apoptosis; moreover, 6-month treatment with lansoprazole in mouse models significantly decreased femoral BMD, in a dose-dependent manner. (13) Metabolomics is a promising agnostic tool to better understand metabolic changes induced by PPI use, and for identifying molecular biomarkers of PPI-mediated BMD loss. Several animal and human studies have been carried out to identify metabolites associated with low BMD and osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…( 12 ) A recent in vitro study using the mouse osteoblast cell line MC3T3‐E1 showed that lansoprazole could lead to intracellular calcium overload, inducing endoplasmic reticulum stress and causing osteoblast apoptosis; moreover, 6‐month treatment with lansoprazole in mouse models significantly decreased femoral BMD, in a dose‐dependent manner. ( 13 )…”
Section: Introductionmentioning
confidence: 99%